Determinants of Fraud Tendency With Internal Control System (SPI) as a Moderating Variable (Study of Savings and Loan Cooperatives in Sikka District) - Fransiska Trisyami Irmayati Subu; Lilis Ardini; Kurnia Kurnia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to test the effect of fraud diamond theory on fraud tendencies with internal control systems as moderating variables. This study uses 135 sample data taken using a purposive method based on criteria. The research method used is quantitative with a survey approach. The data used in this study is a questionnaire. Data analysis using Moderated Regression Analysis. The study's results indicate that rationalization and capability positively affect fraud tendencies and internal control systems moderate the effect of capability on fraud tendencies. The results also show that pressure and opportunity do not affect fraud tendencies while internal control systems do not moderate the effect of pressure, opportunity, and rationalization on fraud tendencies. Based on the results of the study, savings and loan cooperatives in Sikka Regency do not provide pressure but provide motivation and compensation to meet every need and improve the internal control system.